Real exchange rate and international reserves in an era of growing financial and trade integration - Joshua Aizenman; Daniel Riera-Crichton (University of California, Santa Cruz Institute for International Economics (SCIIE), 2006)
This paper evaluates the impact of international reserves, terms of trade shocks and capital flows on the real exchange rate (REER). We observe that international reserves cushions the impact of TOT shocks on the REER, and that this effect is important for developing but not for industrial countries. This buffer effect is especially significant for Asian countries, and for countries exporting natural resources. Financial depth reduces the buffer role of IR in developing countries. Developing countries REER seem to be more sensitive to changes in reserve assets; whereas industrial countries display a significant relationship between hot money and REER.
Keywords: F15; F21; F32; F36; 330; real exchange rate; terms of trade; international reserves; volatility; shock absorber; Kaufkraftparität; Währungsreserven; Terms of Trade; Volatilität; Welt